Cistercians, Recluses and Salvation Networks in the Thirteenth Century - Easterling, Joshua S. (Quaderni di storia religiosa medievale, 2021)
As Cistercian communities expanded across Europe and England, they fostered close ties with anchorites, who often depended on direct spiritual assistance from their monastic neighbours. By the latter half of the thirteenth century, however, these salvation networks experienced a notable decline. Early spiritual bonds with Cistercians, which especially benefited female recluses, met with the rapid changes within the culture of voluntary reclusion, including its expansion within urban centres and the concomitant rise of mendicant and clerical influence on the lives of local recluses. Together with the increased presence of laypeople at the anchoritic cell, these developments rendered the question of spiritual oversight both more complex and more urgent.